The position and role of religious figures in the state structure of traditional Kazakh society - Arystanbekuly, N.; Issakhan М. (Eurasian Journal of Religious Studies, 2025)
The article provides a comprehensive analysis of the formation and development of the institution of religious functionaries in traditional Kazakh society, as well as their role in social, legal, and spiritual life. The main objective of the study is to identify the social functions of khojas, ishans, akhuns, qadis, muhtasibs, and mullahs from the period of the Kazakh Khanate through the nineteenth and twentieth centuries, and to examine, from a scholarly perspective, the model of interaction between customary law and Islamic sharia. The study advances the idea that, in traditional Kazakh society, the relationship between religion and the state was characterized by limited religious authority alongside a high level of spiritual influence. The scientific significance of the research lies in the systematization of a local, synthetic model of religious hierarchy in Kazakh society based on historical sources. Its practical value consists in the possibility of using the findings in academic courses on religious studies, history, law, and cultural studies, as well as in the analysis of religious issues in secular societies. The methodological framework of the study includes comparative-historical analysis, systems analysis, cross-cultural approaches, and methods of religious studies interpretation. The results demonstrate that customary law and Islamic sharia functioned in close interaction in Kazakh society, while religious functionaries, remaining outside direct political power, exerted substantial spiritual authority. The article contributes to a deeper understanding of the religious and social history of the Kazakh people and to the incorporation of their spiritual heritage into academic discourse. Keywords: Islam, Sharia, Khoja, Muhtasib, Mullah